Improving Aliyah Students’ Speaking Skills by Using Podcast - Harisna Hikmah; Wahyu Nugroho; Ulul Azmi (Universitas Pahlawan Tuanku Tambusai, 2021)
This research is aimed in improving students’ speaking skills for Aliyah students at grade XII by using Podcast media. The background of this research is the need of technology application in the teaching and learning process in covid-19 pandemic. This research applied quasi experimental method with pre-test post-test design. The sample of this study are female students of grade XII IPS as the experimental class and female students of XII IPA for the control class. The instruments used to collect the data are speaking test and questionnaire. The speaking test used to gather the data about speaking achievement, while the questionnaire used to obtain the data on students’ perspective of using Podcast in speaking teaching and learning process. To analyze the data, the researcher used normality, homogeneity, and t-test. While descriptive statistics is used to analyze the data on students’ perspective. The result of independent sample t-test is 0.014 means it is lower than 0.05. So, it can be concluded that there is a significant difference between control and experimental group. While for the students’ perspective of the use of Podcast in the English teaching and learning process found most of the students have positive respond. Most of them said that Podcast can help them in learning English, especially in speaking skills.